Determination of Quantity Fertilizer for Sugarcane Based on Wireless Sensor Network - Adinda Abdillah; Muhammad Nanak Zakaria; Waluyo Waluyo (Jurnal Jaringan Telekomunikasi, 2022)
Fertilization plays a very large role in crop yields if done in the right way, effective and efficient fertilization will be achieved if the soil fertility conditions are known in advance. However, the problem is that farmer fertilization is still carried out by means of estimates based on land area without estimating the factor of soil needs.In this study the system uses a Wireless Sensor Network where there are 2 nodes installed on the land to monitor the measurement of soil moisture, soil pH, and nutrients using soil moisture sensors, soil pH sensors, and NPK sensors. From these sensors, it will be integrated through the Arduino Uno microcontroller which will later be connected to the LoRa system to send measurement information data on the land to the raspberry pi.The communication system between nodes is designed with a peer to per topology. The results of this study are the use of appropriate fertilizers and then can restore soil conditions to ideal soil conditions. From the experimental results, it is found that the peer to peer communication system can work well.